Hybrid analytical–numerical–experimental study of low-frequency transformer noise control using stacked Helmholtz resonator panels - Mohammad, Suleiman Ibrahim; Maashari, Naeema Darwish Khamis Al; Vasudevan, Asokan; Wu, Wenya; Hunitie, Mohammad Faleh Ahmmad; Mohammad, Anber Abraheem Shlash; Al-Fawwaz, Torki M. (Sound & Vibration, 2026)
Low frequency noise produced by electrical transformers is one of the most resilient problems, since such types of noises are highly resistant to standard techniques of noise suppression. Absorption panels do not provide sufficient protection below 500 Hz; hence, alternative techniques based on resonance have been developed in the field of passive acoustic control. This research considers stacked Helmholtz resonators as a possible method of attenuating low frequency noises produced by transformer equipment in the range from 20 Hz to 500 Hz. A combination of analytical, numerical, and experimental techniques is utilized to estimate the effectiveness of the proposed method. Experimental tests have shown that proper configuration of Helmholtz resonators can help to attenuate sounds up to 7.5 dB and provide 9.2 dB of transmission loss. The highest efficiency of attenuation has been estimated at 11.5%. Numerical estimates demonstrated a high level of correspondence with experiments, with an error margin of smaller than 3.2% for all tested configurations. An increase in the volume of cavities, neck lengths, and layering significantly increased the efficiency of low frequency attenuation. It can be concluded that the application of stacked Helmholtz resonator panels is one of the most energy-efficient ways to suppress noise in the considered low-frequency band.